2000 Year-old Bogong moth (Agrotis infusa) Aboriginal food remains, Australia - Birgitta Stephenson (Nature Portfolio, 2020)
Abstract Insects form an important source of food for many people around the world, but little is known of the deep-time history of insect harvesting from the archaeological record. In Australia, early settler writings from the 1830s to mid-1800s reported congregations of Aboriginal groups from multiple clans and language groups taking advantage of the annual migration of Bogong moths (Agrotis infusa) in and near the Australian Alps, the continent’s highest mountain range. The moths were targeted as a food item for their large numbers and high fat contents. Within 30 years of initial colonial contact, however, the Bogong moth festivals had ceased until their recent revival. No reliable archaeological evidence of Bogong moth exploitation or processing has ever been discovered, signalling a major gap in the archaeological history of Aboriginal groups. Here we report on microscopic remains of ground and cooked Bogong moths on a recently excavated grindstone from Cloggs Cave, in the southern foothills of the Australian Alps. These findings represent the first conclusive archaeological evidence of insect foods in Australia, and, as far as we know, of their remains on stone artefacts in the world. They provide insights into the antiquity of important Aboriginal dietary practices that have until now remained archaeologically invisible.